Computational simulation applied in choosing the best solution in a product development using design for manufacturing and assembly approach - Pinheiro, Nathália Marcia Goulart (2018)
Highlights: The product development methodology aims to assist the planning and design of the product throughout its life cycle. Using selection criteria it is possible to choose a solution will be followed until the end of the development process and this process is known as optimization of product solutions. Design for Manufacturing and Assembly (DFMA) is an approach that allows selecting a product solution with better manufacturing and assembly performance. Computational modeling allows representing systems in virtual environment in order to reproduce its characteristics and to compare scenarios through simulation. Goal: The objective of this work was to apply the computer simulation to compare the productive performance, according to production times, productivity and resource utilization rate, of three solutions proposed for a raincoat for pets with thermal protection. Methodology: Initially, conceptual models representing the production systems for the three product solutions were generated. The systems were modeled in discrete event simulation software, enabling different scenarios testing, resulting in production performance indicators for each product solution. Results: The analysis of the performance indicators allow identifying that the third solution proposed for the product obtained the best productive performance in all proposed scenarios; therefore, it was chosen as the best solution for the product according to the DFMA approach. Limitations of the investigation: The application of the methodology indicated in this work was limited to the study of a single productive system of a specific product. Practical implications: This work presents a practical application of computer simulation tools applied to product development. Originality / Value: The original contribution of this work is the application of computational simulation of production systems in product development following the DFMA approach.